2015
DOI: 10.1016/j.cct.2015.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Motivational tools to improve probationer treatment outcomes

Abstract: Background Motivational interviewing (MI) is a promising practice to increase motivation, treatment retention, and reducing recidivism among offender populations. Computer-delivered interventions have grown in popularity as a way to change behaviors associated with drug and alcohol use. Methods/Design Motivational Assistance Program to Initiate Treatment (MAPIT) is a three arm, multisite, randomized controlled trial, which examines the impact of Motivational Interviewing (MI), a Motivational Computer Program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 54 publications
(50 reference statements)
0
15
0
Order By: Relevance
“…Research on motivational interventions for CJS-involved individuals is growing and there already are promising findings of increased treatment retention for adults in outpatient treatment (Lincourt, Kuettell, & Bombardier, 2002) and substance use outcomes among adolescents supervised by the juvenile justice system (Stein et al, 2011). Others also are examining the benefits of in-person and computer delivered motivational interviewing strategies with probationers (Taxman, Walters, Sloas, Lergch, & Rodriguez (2015). Utilizing brief interventions that target motivation could be helpful in improving treatment, substance use, and criminal recidivism outcomes for incarcerated individuals with AUDs being released from jail.…”
Section: Introductionmentioning
confidence: 99%
“…Research on motivational interventions for CJS-involved individuals is growing and there already are promising findings of increased treatment retention for adults in outpatient treatment (Lincourt, Kuettell, & Bombardier, 2002) and substance use outcomes among adolescents supervised by the juvenile justice system (Stein et al, 2011). Others also are examining the benefits of in-person and computer delivered motivational interviewing strategies with probationers (Taxman, Walters, Sloas, Lergch, & Rodriguez (2015). Utilizing brief interventions that target motivation could be helpful in improving treatment, substance use, and criminal recidivism outcomes for incarcerated individuals with AUDs being released from jail.…”
Section: Introductionmentioning
confidence: 99%
“…A strength of choosing these two diverse sites was the ability to generalize these findings to other probation systems (see Taxman, et al, 2015 for a description of site differences). To test the generalizability of these findings, we ran the models with site included as a covariate (not reported) and found that the effects of the interventions did not change.…”
Section: Discussionmentioning
confidence: 99%
“…This study has a few limitations discussed elsewhere (e.g., inability to verify self-reported treatment initiation) (Taxman, et al, 2015). One additional limitation to this study is the challenge of determining the mechanism within each study arm that most impacted the outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants completed a baseline assessment, and follow-up interviews at two and six months. Full trial details can be found elsewhere (Taxman, Walters, Sloas, Lerch, & Rodriguez, 2015). …”
Section: Methodsmentioning
confidence: 99%